Investigation of the effect of the COVID-19 pandemic on the logistics activities of businesses - Ersöz, Atakan (My University, 2023)
Lojistik sektörü her ülkenin sosyal ve ekonomik kalkınmasında en önemli yere sahiptir. Firmaların üretimden müşteriye teslimine kadar tüm ticari faaliyetlerinin etkin bir şekilde izlenmesini gerektirir. Aralık 2019'da başlayan ve etkisini tüm dünyada hissettiren Covid-19 pandemisi, lojistik ve tedarik zincirini de ciddi şekilde etkilemiştir. Pandemi ile sektörde taşınması gereken malların aktarılması ve depolanması problemleri ortaya çıkmıştır. Bu tez çalışmasının amacı, Covid-19 pandemi sürecinin, Türkiye'de lojistik hizmet veren firmaları veya lojistik birimleri bulunan üretim firmaları üzerindeki etkilerini araştırmaktır. Bu kapsamda firmalardan 2020-2021 yıllarını kapsayan Covid-19 pandemisindeki etkilerine ilişkin veriler anket yoluyla elde edilmiştir. Öncelikle pilot çalışmada firmalardan elde edilen verilere Açıklayıcı Faktör Analizi (EFA) uygulanmış ve ölçeğin güvenirlilik ve geçerliliği araştırılmıştır. Oluşturulan güvenilir ve geçerli anket soruları Google platformu üzerinden Türkiye'deki firmalara gönderilmiştir. Firmalardan elde edilen veriler yardımıyla pandemi sürecinde araştırmanın hipotezleri test edilmiş ve sektörün tanımlayıcı istatistikleri ortaya konulmuştur. Ayrıca pandeminin lojistik hizmetine olan etkisi çoklu doğrusal regresyon analizi ile ortaya çıkarılmış ve korelasyon analizi ile değişkenler arasındaki ilişkiler araştırılmıştır. Araştırma sonucuna göre; çok uluslu şirketlerin pandemiden bölgesel şirketlere göre maliyet ve tedarik zinciri açısından daha fazla etkilendiği; firmaların teknolojisine ve dijitalleşmesine göre çok uluslu şirketlerin bölgesel ve yerel şirketlere göre daha fazla etkilendiği ve çalışan sayısı az olan şirketlerin, çalışan sayısı yüksek şirketlere göre pandemiden daha fazla etkilendiği belirlenmiştir.

The logistics sector has the most important place in the social and economic development of every country. It requires effective monitoring of all commercial activities of companies from production to delivery to the customer. The Covid-19 pandemic, which started in December 2019 and made its impact felt all over the world, also seriously affected the logistics and supply chain. With the pandemic, the problems of transferring and storing the goods that need to be transported in the sector have emerged. The aim of this thesis study is to investigate the effects of the Covid-19 pandemic process on companies providing logistics services or manufacturing companies with logistics units in Turkey. In this context, data on the effects of the Covid-19 pandemic covering the years 2020-2021 were obtained from the companies through a survey. First, Exploratory Factor Analysis (EFA) was applied to the data obtained from the companies in the pilot study and the reliability and validity of the scale were investigated. The created reliable and valid survey questions were sent to companies in Turkey via the Google platform. With the help of the data obtained from the companies, the hypotheses of the research were tested during the pandemic process and the descriptive statistics of the sector were revealed. In addition, the effect of the pandemic on the logistics service was revealed by multiple linear regression analysis and the relationships between the variables were investigated by correlation analysis. According to the results of the research; multinational companies were more affected by the pandemic than regional companies in terms of cost and supply chain; It has been determined that multinational companies are more affected than regional and local companies according to the technology and digitalization of companies, and companies with a low number of employees are more affected by the pandemic than companies with a high number of employees.
COVİD-19 pandemisinin işletmelerin lojistik faaliyetleri üzerindeki etkisinin araştırılması
Keywords: Business logistics; COVID-19 (Disease); COVID-19 (Hastalık); Covid-19; İşletme lojistiği; Lojistik; Pandemi Etkis Logistic; Pandemic Effect; Supply Chain; Tedarik Zinciri